Measurement of the differential cross-sections of prompt and non-prompt production of [Formula: see text] and [Formula: see text] in pp collisions at [Formula: see text] and 8 TeV with the ATLAS detector - Aad, G; Abbott, B; Abdallah, J; Abdinov, O; Aben, R; Abolins, M; AbouZeid, O S; Abramowicz, H; Abreu, H; Abreu, R; Abulaiti, Y; Acharya, B S; et al. (The European physical journal. C, Particles and fields, 2016)
The production rates of prompt and non-prompt [Formula: see text] and [Formula: see text] mesons in their dimuon decay modes are measured using 2.1 and 11.4 fb[Formula: see text] of data collected with the ATLAS experiment at the Large Hadron Collider, in proton-proton collisions at [Formula: see text] and 8 respectively. Production cross-sections for prompt as well as non-prompt sources, ratios of [Formula: see text] to [Formula: see text] production, and the fractions of non-prompt production for [Formula: see text] and [Formula: see text] are measured as a function of meson transverse momentum and rapidity. The measurements are compared to theoretical predictions.